Financing The Development of Artificial Intelligence Maid: An Analysis Of Pertinent Fiqhi Issues - Miszairi bin Sitiris; Saheed Abdulahi Busari; Mohd Fuad bin Md. Sawari; Muntaha Artalim Zaim (USIM Press, 2024)
Journal of Fatwa Management and Research (JFatwa) Volume 28 No.3 Page (21-40)